Layer-specific stem cell differentiation in tri-layered tissue engineering biomaterials: Towards development of a single-stage cell-based approach for osteochondral defect repair - Kelly, Daniel (My University, 2021)
Successful repair of osteochondral defects is challenging, due in part to their complex gradient nature. Tissue engineering approaches have shown promise with the development of layered scaffolds that aim to promote cartilage and bone regeneration within the defect. The clinical potential of implanting these scaffolds cell-free has been demonstrated, whereby cells from the host bone marrow MSCs infiltrate the scaffolds and promote cartilage and bone regeneration within the required regions of the defect. However, seeding the cartilage layer of the scaffold with a chondrogenic cell population prior to implantation may enhance cartilage tissue regeneration, thus enabling the treatment of larger defects. Here the development of a cell seeding approach capable of enhancing articular cartilage repair without the requirement for in vitro expansion of the cell population is explored. The intrinsic ability of a tri-layered scaffold previously developed in our group to direct stem cell differentiation in each layer of the scaffold was first demonstrated. Following this, the optimal chondrogenic cell seeding approach capable of enhancing the regenerative capacity of the tri-layered scaffold was demonstrated with the highest levels of chondrogenesis achieved with a co-culture of rapidly isolated infrapatellar fat pad MSCs (FPMSCs) and chondrocytes (CCs). The addition of FPMSCs to a relatively small number of CCs led to a 7.8-fold increase in the sGAG production over chondrocytes in mono-culture. This cell seeding approach has the potential to be delivered within a single-stage approach, without the requirement for costly in vitro expansion of harvested cells, to achieve rapid repair of osteochondral defects
Keywords: osteochondral defects; layered scaffolds; host bone marrow MSCs; osteochondral defects; layered scaffolds; host bone marrow MSCs